Soil magnetic susceptibility for estimating the support capacity to vinasse application - Peluco, Rafael Gonçalves; Marques Júnior, José; Siqueira, Diego Silva; Pereira, Gener Tadeu; Barbosa, Ronny Sobreira; Teixeira, Daniel De Bortoli; Adame, Cássia Rita; Cortez, Lucas Aguilar (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the magnetic susceptibility efficiency for estimating the support capacity of areas for vinasse application. Two hundred forty‑one soil samples were collected from a 380‑ha area, on which soil chemical properties, clay content, and magnetic susceptibility were determined. Vinasse requirement was calculated for each sample. Data were subjected to descriptive statistical analysis, and regression models were developed between magnetic susceptibility and the other evaluated attributes. The analysis of data spatial dependence was performed using geostatistics. Kriging maps and cross variograms were built in order to investigate the spatial correlation between soil magnetic susceptibility and studied attributes. Based on the map of vinasse requirement, on the soil classes, and on the kriging map, calculations were done for average vinasse dose and average soil support capacity, weighted by the area. Magnetic susceptibility has significant linear spatial correlation with recommended vinasse doses and soil support capacity for the application of this effluent, and it can be used as a pedotransfer function for indirect quantification of soil support capacity.